Practice and the History of Science in the PRC: A Historiographic Reflection. Issue 3 (1st September 2019) - Fu, Jia-Chen
Abstract: Recent scholarship on the history of science in the People's Republic of China (PRC) has provided new horizons for exploring questions about the nature and epistemology of socialist science, its epistemic virtues, its knowledge-producing practices, its geographical imagination and networks of communication and exchange, and its relations to the Chinese state and state building. In this essay the author uses a focus on practice to extrapolate implications and tendencies that he sees as unifying recent studies, and he clarifies their contributions to the current understanding of the history of science in the PRC. Particularly with respect to Chinese state-science relations and the nature of Maoist mass science, a focus on practice illuminates how recent scholarship has queried and interrogated unitary conceptions of the Chinese state and science, highlighted transnational connections and movements, and deepened our understanding of Maoist mass science.